2011
DOI: 10.1016/j.molonc.2011.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Studies of genomic copy number changes in human cancers reveal signatures of DNA replication stress

Abstract: A B S T R A C THuman cancers are characterized by the presence of genomic instability. Recently, two studies have catalogued the presence of a specific class of genomic aberrations, large deletions and insertions, in a few thousand human cancers and reported that most of the prevalent recurrent focal deletions targeted common fragile sites and large genes. In various experimental systems, deletions in common fragile sites and large genes have been linked to the presence of DNA replication stress. Thus, taken t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 50 publications
2
56
0
Order By: Relevance
“…Overall, the characterization of oncogene-induced FSs demonstrates that they share prominent features with aphidicolin-induced FSs such as colocalization with cancer genomic instability hotspots and large genes. Our results showing an overlap between oncogene-induced FSs and large genes further support the possibility that most large genes are actually FSs under specific replication stress conditions that were not yet discovered 18,27 .…”
Section: Discussionsupporting
confidence: 80%
“…Overall, the characterization of oncogene-induced FSs demonstrates that they share prominent features with aphidicolin-induced FSs such as colocalization with cancer genomic instability hotspots and large genes. Our results showing an overlap between oncogene-induced FSs and large genes further support the possibility that most large genes are actually FSs under specific replication stress conditions that were not yet discovered 18,27 .…”
Section: Discussionsupporting
confidence: 80%
“…Genes encoding proteins that are implicated in the EGFR/PI3K pathway are labeled in red. DNA alterations are known to be influenced by chromatin structure and features of the neighboring DNA sequence (40,41). Our data here suggest that CNAs in these four components of the EGFR/PI3K pathway are important for pathway activation in HNSCC, although we cannot definitively rule out involvement of other genes within the regions of CNA.…”
Section: Protein Tyrosine Phosphatase Receptor S (Ptprs) Is Frequentlymentioning
confidence: 58%
“…Incomplete replication causes DNA damage and has been linked to rearrangements at common fragile sites and chromosomal instability, the most common form of genomic instability in sporadic cancers. [45][46][47] Higher levels of origin firing mean that more replication forks are active simultaneously, and it appears likely that replication elongation factors such as deoxyribonucelotides (dNTPs) become limiting under these conditions. Indeed, it was recently reported that Cyclin E overexpression decreased dNTP pools, resulting in decreased replication fork progression and replication stress.…”
Section: Discussionmentioning
confidence: 99%